Association of Bone-related Biochemical Markers and Risk of Prehypertension in Osteoporotic Elders - Sudjaroen, Dr. Yuttana (Asian Journal of Pharmaceutics (AJP), 2018)
Context: The association of bone turnover markers (BTMs) and cardiovascular disease had been representing. Aims: The study aimed to evaluate the association of osteoporosis status and prehypertension in elders, who were indicated by bone related - and cardiovascular risked - biochemical markers. Settings and Design: A cross-sectional study was carried out in Samut Songkhram, Thailand, and 105 elders were joined. Materials and Methods: Bone mineral density (BMD) was measured by calcaneal quantitative ultrasound. BTMs (osteocalcin [OC], Procollagen type 1 N-terminal pro-peptide, Beta-crossLaps [CTX], and alkaline phosphatase [ALP]); bone-related biochemical markers (25-hydroxyvitamin D [25-(OH)D], calcium, phosphorus, and magnesium); lipid profile (cholesterol, triglyceride, high density lipoprotein-cholesterol, and low density lipoprotein); and high sensitive C-reactive protein (hs-CRP) were analyzed using automatic analyzers. Blood pressure measurement was done after resting. Statistical Analysis Used: Descriptive data were represented as a mean ± standard deviation. One-way ANOVA was compared parameters within three elders groups. Pearson’s correlation was tested for the relations of BMD with other parameters. Odds ratio was calculated for risk of prehypertension. Results: BMD was significantly correlated to calcium, phosphorus, and triglyceride in high, low, and very low levels, respectively. Inversely correlations of BMD with CTX and hs-CRP were significant in medium level. Risk of prehypertension was increased 1.12-fold with a decrement of T-score < −1.0. Increment of CTX, hs-CRP, and LDL-C was increased 1.93, 1.94, and 1.31-fold of prehypertension risks, respectively. Conclusions: Prehypertension was associated with osteoporosis, which indicated by inversely correlation of hs-CRP and CTX to BMD; and correlation of serum calcium, phosphorus, and triglyceride to BMD.